Hypophysis and blood pressure - Houssay, Bernardo Alberto (1936)
The posterior pituitary lobe contains vasopressor substances, which in amphibians play a very important role in the maintenance of the blood pressure and arterial and capillary tone. Small quantities of similar substances exist in the principal lobe of the toad, but removal of this lobe causes a lowering of the blood pressure only after asthenia has developed. In the rat, dog and man pituitary insufficiency is accom- panied by lowered blood pressure; it is not clear whether this is due to lack of one or both lobes, but it seems more particularly due to lack of the anterior lobe (central or peripheral vascular asthenia). The existence of raised blood pressure in acromegaly has not been well established, since the blood pressure is frequently normal in these cases. On the other hand hypertension is a constant and prominent symptom in the pitui- tary basophilism syndrome of Cushing, though whether this is due to pituitary or adrenal hy- persecretion or to a secondary or associated factor, is not yet clear. The evidence put forward to demonstrate that hyperactivity of the posterior pituitary lobe is the causal factor in eclampsia and in essen- tial hypertension is contradictory and inconclusive. In contradistinction to the medulla the diencephalon is not essential for the maintenance of blood pressure in acute experiments, nor has it been proved that increase in blood pressure due to lesions or stimulation of this region is accompanied by hypersecretion of the posterior pituitary.